The Participation Processes in Reconciliation for the Reform in Northeast Thailand - Glunpromsuwan, Wanchana (Ratchaphruek Journal, 2014)
This research studied the participation processes in reconciliation reform of Northeast Thailand by using mixed research methodology which consists of 1) Opinion surveys of 207,396 respondents, 2) Sustainable Happiness Forum evaluation form of 868 respondents and, 3) In-depth interview of 60 interviewees. Statistics Principles for data analysis were consist of mean, percentile, and standard deviation. From the research results indicated: 1. From the Opinion survey, the results shown that most of respondents were strongly agree with the current situation in Thailand (especially Political Situation), Coup d’etat, Martial law enforcement, and payment of the rice subsidy program for Thai farmers. 2. The evaluation result from the Sustainable Happiness Forum indicated the most satisfaction for the event. It shown the strongly agree with reasons of seizing power over the government, the declaration of 3-step processes of the administration, current situation in social environment since the previous situation occurred, and the conclusion of the urban area project plan. 3. Data analysis from the responses found that most of the respondents 1) require the government services improvement in care, 2) support for elderly and disabled people, 3) provide agricultural water supply, 4) encourage the sufficiency economy , government service equality, and local waste management.